Sistem Informasi Administrasi Kepegawaian pada Dinas Tenaga Kerja di Kabupaten Mandailing Natal Berbasis Web - Novita Tanjung; Muhammad Arif (LPPM IAI Nasional Laa Roiba Bogor, 2022)
The development of technology and information is currently accelerating, this development has made many conveniences ranging from the use of computer technology to automated management handling. In this study, we will try to create a Web-Based Information System for Personnel Administration at the Office of the Manpower Office in Mandailing Natal Regency which currently uses computers for operation, but the data processing process is still manual. So we need a system that can accelerate performance and be developed more modern in order to operate using a computerized system. The method used in designing and making this web application is the Native Web Method, the programming language used is PHP, and MySQL as data storage. For display design using the Bootstrap AdminLTE Framework which provides basic HTML and CSS templates for the application of typography, forms, buttons, navigation, and many other interface components. This research will produce a Web-Based Personnel Administration Information System at the Wonosobo Regency Regional Secretariat Office which has an appropriate interface so that it can provide information and facilitate the process of managing personnel administration. Keywords: Personnel Administration, AdminLTE, MySQL, PHP, Information Systems. Kata kunci : system,administration, web